Freedom of religion - Beek, A. van de.; Borght, Ed. A. J. G. van der, 1956-; Vermeulen, B. P. (Studies in Reformed Theology, 2010)
The idea of freedom of religion was developed in Europe in the 16th and 17th century in the context of religious diversity as an alternative for religious wars. The concept requires reconsideration in the current globalized culture: religious plurality has increased as has the awareness of the religious potential for social cohesion and for sectarian division and violence. In this volume, legal experts, sociologists, theologians, and philosophers clarify the historical development of the concept, and analyze the present situation in various countries with religious tensions. They propose possible models and solutions, and discuss the fundamental question of whether the Western model of human rights with its separation of religion and state and freedom of religion can be conceived as universal.